Atividade de extratos de espécies arbóreas da caatinga sobre a emergência e desenvolvimento de plântulas de feijão-caupi, melão e milho - Oliveira, Andreya Kalyana de (Universidade Federal Rural do Semi-Árido, 2014)
The objective of this work was to analyze the activity of plants from Caatinga biome on the emergence and development of cowpea, melon and corn seedlings. From November 2011 to June 2012, on Laboratório de Análise de Sementes (UFERSA), the activity of extracts from seeds and leaves of juazeiro (Zizyphus joazeiro Mart.), jucá (Caesalpinia ferrea Mart.), mulungu (Erythrina vellutina Willd.) and cumaru (Amburana cearenses (Allemão) A. C. Smith.) in five levels of concentrations (1, 0.5, 0.25, 0.125 and 0%), in corn seeds (Zea. mays L.), melon (Cucumis melo L) and cowpea (Vigna unguiculata (L) Walp.). These tests corresponded to the first experimental part, in which each species and its respective organ integrated an experiment (E1, E2, E3 extracts of seeds of juazeiro on corn, melon and cowpea and E4, E5, E6 extracts of leaves of juazeiro on corn, melon and cowpea). On the second part of the study, it was made a fractionation of the extract of cumaru seeds with the solvents hexane, dichloromethane, ethyl acetate and water, where the activity of these extracts on the initial development of melon seeds was tested, as each portion with its respective dilution formed an experiment (E1 hexane fraction (1, 0.5, 0, 25, 0,.25, 0%), E2 dichloromethane fraction (1, 0.5, 0.25, 0.125, 0%), E3 - ethyl acetate fraction (1 and 0%), E4 water fraction (1 and 0%). On the last part, it was made a phyto-chemical prospection of the extracts resulting from the previous stage. The preparation of the dry and aqueous extracts used in this experiment, phyto-chemical prospection and fractionation were accomplished on Laboratório de Análise Cromatográfica (UERN) from November 2011 to February 2013. Statistical design was completely randomized with four replications with twenty seeds. Treatments were formed by the concentrations 1, 0.5, 0.25, 0.125 and 0%, corresponding to each extract. The evaluation of the behavior of the litmus test was made through the analysis of the percentage and emergence speed index characters, percentage of normal seeds, dry matter, aerial parts length and root and number of roots on corn. The averages were compared by Tukey test, at 5% possibility, analyzed by the statistical program SISVAR. In the end of the experimental analysis, we may conclude that leaves and seeds of the Caatinga biome species influenced reducing or increasing the average of the variables used on the evaluation of corn, melon and cowpea seeds development, and the effects were greater when in the presence of cumaru seeds extract. The extracts obtained from the hexane portion provided adverse effects on melon seeds development. Cumarina was the dominant composite on the phyto-chemical prospection on the cumaru seed extract
Extracts acitivity of tree species from Caatinga on the emergence and development of cowpea, melon and corn seeds
Keywords: Amburana Ceará; Railway Caesalpinia, Mart .; Zizyphus joazeiro, Mart .; Erythrina vellutina, Willd .; Bioactive substances; Amburana cearenses; Caesalpinia férrea, Mart.; Zizyphus joazeiro, Mart.; Erythrina vellutina, Willd.; Substâncias bioativas; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA